2017
DOI: 10.1016/j.gaitpost.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Altered spatiotemporal characteristics of gait in older adults with chronic low back pain

Abstract: Previous studies in older adults have identified that chronic low back pain (CLBP) is associated with slower gait speed. Given that slower gait speed is a predictor of greater morbidity and mortality among older adults, it is important to understand the underlying spatiotemporal characteristics of gait among older adults with CLBP. The purposes of this study were to determine (1) if there are differences in spatiotemporal parameters of gait between older adults with and without CLBP during self-selected and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 32 publications
2
34
0
2
Order By: Relevance
“…Data are presented for each patient; horizontal bar represents median with 95% confidence intervals Gait is an important indicator of health and can be influenced by many variables [16,[22][23][24]. Older adults with chronic low back pain exhibit significantly different gait patterns compared to age-and sex-matched adults without chronic low back pain [25]. In the current study, it was demonstrated that only two of all measured gait parameters improved and returned to "healthy" levels after 6 months of conservative treatment (self-selected gait speed and stride time at 1 m/s).…”
Section: Discussionmentioning
confidence: 99%
“…Data are presented for each patient; horizontal bar represents median with 95% confidence intervals Gait is an important indicator of health and can be influenced by many variables [16,[22][23][24]. Older adults with chronic low back pain exhibit significantly different gait patterns compared to age-and sex-matched adults without chronic low back pain [25]. In the current study, it was demonstrated that only two of all measured gait parameters improved and returned to "healthy" levels after 6 months of conservative treatment (self-selected gait speed and stride time at 1 m/s).…”
Section: Discussionmentioning
confidence: 99%
“…A review of existing publications indicates that around 20% of patients experience progression of the symptoms, 19 the morbidity and mortality rates increase with age, and complications are more common in elderly patients. [20][21][22] This condition is not sex-dependent. The most affected age ranges in our study were from 46 to 65 years of age, which agrees with those reported by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Following the title andabstract screening, 35 fulltext articles were retrieved. The full-text review was completed to determine nal inclusion; 17 articles (13 case-control studies [20][21][22][23][24][25][26][27][28][29][30][31][32] , four RCTs [33][34][35][36] ) met the inclusion criteria. Only the 13 case-control studies were included in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…------TUG One-leg stance Walking speed Hicks(2018) [30] case-control 69. 3 Silva(2016) [31] case-control 70.0 8 10 73.0 (7)…”
mentioning
confidence: 99%